Qualidade do sono em gestantes de risco habitual e alto risco: um estudo comparativo - Holanda, Sâmia Monteiro (2017)
The preparation of the female organism for pregnancy involves a multitude of adjustments, where typical characteristics appear that permeate the most common complaints of this period. Studies have shown the association between gestational discomforts and poor sleep quality. It is known that gestation itself is a factor that interferes with sleep and, since this pregnancy is at high risk, it may accumulate to the physiological impacts of the gestational risk motive the concern with maternal and fetal health, thus causing a quality of sleep even worse. It is necessary to evaluate sleep in pregnant women, since its poor quality is related to varied risk conditions in pregnancy and undesirable maternal and neonatal outcomes. Therefore, the objective of the study is to compare sleep quality among pregnant women at normal and high risk. This is a cross-sectional comparative study conducted between August and November 2017 with 100 pregnant women at normal risk and 110 at high risk, using the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESE), both validated for the Brazilian population, to assess sleep quality, as well as the sociodemographic, clinical and obstetrical instrument. The majority of pregnant women in both groups have an average of 25 years, 11 years of schooling and earn 1.5 minimum wages, live with a partner, do not work and are brown. The average gestational age for the usual risk was 25 weeks and for high risk was 26 weeks, most were classified with adequate BMI, did not perform physical activity and denied previous sleep complaint. Pregnant women with normal risk of getting pregnant are on average at 21:50, taking about 30 minutes to fall asleep and sleeping an average of 7:50 hours a night. The high-risk patients lie on average at 21:00, take about 58 minutes to fall asleep and sleep an average of 6:30 hours a night. The mean overall PSQI score was 5.98 for the first group and 9.36 for the second group (p = 0.00), the mean overall ESS score was 8.86 for pregnant women at usual risk and 10 , 49 for those at high risk. Among the pregnant women at risk 65% (n = 65) had a score> 5 in the PSQI, for high-risk pregnant women, this number corresponded to 91.2% (n = 101). It is concluded that both groups have poor sleep quality, but this intensity is higher in high-risk pregnant women, with a greater amount of excessive daytime sleepiness.